Ein Ensemble ungewöhnlicher Reliefs im Militärpalast von Ninive - Miglus, Peter A. (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2022)
Out of the looting tunnels on Tell Nebi Yunus at Nineveh, which were dug into the ruins of the Late Assyrian military palace by henchmen of the so-called Islamic State, there came, amongst other objects, relief panels featuring anthropomorphic representations. These figures, shown in frontal view, are unusual when compared to the wider repertoire of Assyrian images known from the royal palaces on Kuyunjik. The decoration and context of these stone slabs raise questions regarding their function.
Online veröffentlicht: 11. Dezember 2021
Gesehen am 16.08.2024